REVIEW OF THE THEORY AND PRACTICE OF COGNITIVE BEHAVIORISTIC GROUP COUNSELING APPROACHES - Bakhrudin All Habsy; Renovaliano Firdiansyah Putri; Rahma Naadira Nursani; Watik Qurrotu A'yunin (Jurnal Kajian Pendidikan dan Psikologi, 2024)
This study aims to explore the effectiveness and challenges of implementing the Cognitive Behavioral Group Therapy (CBT) approach in group settings. Through a literature review methodology, this research analyzes relevant literature to understand how CBT theories and techniques are adapted and applied in groups, and how group dynamics influence the outcomes of therapy. The literature review involves a systematic search and critical analysis of journal articles, books, and previous studies discussing the effectiveness, dynamics, and adaptation of CBT techniques in group settings. The findings of the study indicate that CBT in a group format has proven effective in addressing various psychological issues, such as depression and anxiety, with group dynamics playing a crucial role in reinforcing the change process. However, significant challenges were identified in adapting techniques that are typically applied in individual settings, particularly in dealing with cultural differences and the diverse social backgrounds of group members. Additionally, the study emphasizes the importance of adequate training for facilitators to manage group dynamics and effectively implement CBT techniques. The conclusion of this research is that group-based CBT holds great potential as an effective intervention for supporting mental health, but it requires careful adaptation and management to achieve optimal results.